PENGARUH METODE STERILISASI DAN KONSENTRASI FILTRAT BAKTERI ENDOFIT TANAMAN TEBU UNTUK MENGENDALIKAN PENYAKIT BLENDOK (Xanthomonas albilineans (Ashby) Savulescu 1947) - Astri Afriani (Jurnal Pertanian Tropik, 2017)
Leaf scald (Xanthomonas albilineans) is an important pathogen of sugar cane in Indonesiaand cause significant losses at several main sugarcane plantations. Some control measures, e.i.bactericides smeared Lysol 20% or alcohol 70% on cutting knife seedling for disinfectant,and hot water treatment at 50 minutes on 52,5ᵒC, have not given satisfactory results inmanaging this leaf scald in sugarcane on the field. Biological control with filtrate ofendophytes bacterial were alternative to biocontrol agents Xanthomonas albilineans. Theobjectives of this research were to determine: influence of sterilization methods andendophytic bacterial filtrate dosages of sugarcane to control leaf scald (Xanthomonasalbilineans). This research was conducted in Phytopathology Laboratory at the Faculty ofAgriculture University of North Sumatra from April until December 2014. This research haddone with Completely Randomized Design (CRD) with three-factor: 1. type of endophyticbacterial filtrates: filtrate of B2, B7 and B9 Sterilization methods of endophytic bacterialfiltrate: control (no sterilization), Sterilization by autoclave and Sterilization by filtermembrane, 3. Dosage of endophytic filtrate with four-level: 0,1%, 0,01%, 0,001% and0,0001%. The result showed: 10 isolate endophytic bacteria had exploration were: B1, B2,B3, B4, B5, B6, B7, B8, B9, and B10. Three isolates had a clear zone on Petri dish ≥ 20 mm invitro testing is B9, B7, and B2. The results showed that the membrane filter sterilizationmethod was better when compared to autoclave sterilization, namely: the highest inhibitoryzone diameter of endophytic bacteria in the treatment of B9 filtrate with a membrane filtersterilization method 0,1% at 3 days after inoculation that was equal to 23.00 mm.